Perampanel-Induced Cataplexy in a Young Male with Generalized Epilepsy. (April 2021) - Kenaan, Kelsey; Zafar, Mohsin; Bond, Ronnie; Gracious, Barbara
Abstract: Perampanel is an anti-epileptic drug reported to exert its effects in the central never system (CNS) by inhibiting post-synaptic glutamate receptors. The most commonly reported neuropsychiatric side effects are affective dysregulation with some reports of psychosis. However, the precise therapeutic mechanism is unknown. We report on a 32-year-old African American male with recurring generalized tonic-clonic (GTC) seizures, who presented to our hospital with onset of mood lability for several months, subsequent to adding perampanel to his antiepileptic medications. On presentation, perampanel administration was temporarily withheld, and subsequently, noted to be coincident with neuropsychiatric symptomatology, including motor weakness in emotional contexts. The mechanisms underlying cataplexy are complex and, in our patient, most likely induced by an interaction between perampanel and the wakeful inhibition of the sublaterodorsal nucleus projections.